Communicating governments: a three-country comparison of how governments communicate with citizens - Sanders, Karen; Canel Crespo, María José; Holtz-Bacha, Christina (International Journal of Press-Politics, 2011)
Various studies have attempted to conceptualize and assess professionalization of political communication from different perspectives. This article examines the professionalization of central government communication in Germany, Spain, and the United Kingdom, applying a framework developed using indicators derived from the sociology of work and from the strategic planning and quality literature. Results show that there are clear indices of the development of formal rules governing the practice of policy-or information-related government communication, distinguishing it from more partisan, politicized communication. Although mechanisms are being introduced to improve the process of communication, practices are still far from being fully systematized. The analysis provides evidence that professionalization as indicated by the establishment of specialist education, of self-regulation, and of formal organization of communication processes can be found at varying speeds in the three countries. The article finally discusses whether the logic of professionalism is compatible with government communication that is manipulative. © The Author(s) 2011.
WiSo-Import:2015-03-26:3368
Keywords: comparative research; professionalism; Western Europe